Platinum(ii) and palladium(ii) complexes with electron-deficient meso-diethoxyphosphorylporphyrins: synthesis, structure and tuning of photophysical properties by varying peripheral substituents. Issue 24 (29th May 2019) - Volostnykh, Marina V.; Borisov, Sergey M.; Konovalov, Mikhail A.; Sinelshchikova, Anna A.; Gorbunova, Yulia G.; Tsivadze, Aslan Yu.; Meyer, Michel; Stern, Christine; Bessmertnykh-Lemeune, Alla
Abstract : The luminescence quenching by O2 and photodegradation of Pt(ii ) and Pd(ii ) phosphorylporphyrins are reported. Abstract : A series of electron-deficient platinum(ii ) and palladium(ii ) meso -(diethoxyphosphoryl)porphyrins, namely [10-(diethoxyphosphoryl)-5, 15-bis( p -tolyl)porphyrinato]palladium(ii ) (PdDTolPP ), 10-(diethoxyphosphoryl)-5, 15-bis[ p -(methoxycarbonyl)phenyl]porphyrinatopalladium(ii ) [PdD(CMP)PP ], [10-(diethoxyphosphoryl)-5, 15-dimesitylporphyrinato]palladium(ii ) (PdDMesPP ), [5-(diethoxyphosphoryl)-10, 15, 20-trimesitylporphyrinato]palladium(ii ) (PdTMesPP ) and the corresponding platinum(ii ) compounds, were synthesized and structurally characterized in solution by means of 1 H, 13 C, 31 P NMR spectroscopies and in the solid state by single crystal X-ray diffraction [PdDTolPP, PdD(CMP)PP andPtD(CMP)PP ]. Their optical and photophysical properties (UV-vis absorption, luminescence and excitation spectra, phosphorescence quantum yields and lifetimes) were also determined. The complexes under investigation emit at room temperature in the near-infrared region (670–770 nm). Phosphorescence quantum yields of the palladium(ii ) meso -phosphorylated porphyrins lie in the range of 3.4 to 5.8%, with lifetimes of 633 to 858 μs in deoxygenated toluene solutions at room temperature. The corresponding platinum(ii ) complexes exhibit phosphorescence quantum yields in the range of 9.2 to 11%, with luminescence decay times of 56 to 69 μs. Moreover, effective homogeneous oxygen quenching and good sensitivity in toluene (∼155 Pa −1 s −1 ) were observed for the platinum(ii ) complexes with phosphorylporphyrins in solution. Investigations of the photostability of porphyrinylposphonates and related complexes lacking a phosphoryl group in DMF under irradiation in air using a 400 W vis–NIR lamp demonstrated that photobleaching is strongly dependent on the substituents at the periphery of the macrocycle. Platinum and palladium trimesitylphosphorylporphyrinsPdTMesPP andPtTMesPP exhibit high photostability in DMF solution and seem to be the most potentially interesting derivatives of the series for oxygen sensing in biological samples and the covalent immobilization on solid supports to prepare sensing devices including optic fibers.